Estimasi Carrier Ferquency Offset menggunakan Timing Metric pada Sinyal OFDM - Sari, Yolen Perdana; Tassia, Shelvi Eka (Jurnal Informatika Universitas Pamulang, 2020)
OFDM is one of technology that can be utilized in a variety of telecommunication systems that being widely developed today, for application in LAN, WLAN, 3G, 4G, or 5G. One of the problem faced by the OFDM technology that its sensitivity to Carrier Frequency Offset (CFO) and the lack of synchronization in the OFDM signal. This research aims to design the synchronization that estimates Carrier Frequency Offset (CFO) to obtain synchronization of OFDM signal, where the error of the estimated Carrier Frequency Offset can be obtained, minimized and better than previous studies. The CFO estimation method in this research is using the training symbol on the OFDM symbol and utilize the statistical characteristics of the timing metric. This researchs result shows the Mean Square Error (MSE) of estimated Carrier Frequency Offset to Carrier Frequency Offset input, with range MSE 9.43 x 10-3 at 0 dB SNR input and MSE 1.687 x 10-5 at 30 dB SNR input. If Signal to Noise Ratio is greater, then the value of the mean square error (MSE) will be smaller. The position of the timing metric for timing estimation also affects to CFO estimation. CFO estimation accuracy will be maximized when using maximum timing metric.